2002
DOI: 10.1177/153537020222700719
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response in Mice Over-expressing or Deficient in Growth Hormone

Abstract: Effects of growth hormone (GH) levels on the humoral immune response were investigated in metallothionein I (MT)-bovine (b) GH-transgenic (tg) and GH-deficient Ames dwarf (Prop1 dt–/–) mice. Four-month-old mice were given primary and secondary injections of either normal saline or tetanus toxoid (TT) to induce specific antibody (Ab) production. MT-bGH-tg mice with high peripheral levels of bGH produced less TT-specific Ab than normal nontransgenic (Ntg) littermates, df, or nondwarf (Ndf) control mice. Titers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This likely represents a shift in the distribution of food-derived energy toward other energetically costly processes and in particular, thermogenesis [94]. However, these animals exhibit normal antibody production in response to a strong challenge [95] and exhibit a delay in immunosenesence [21, 88]. …”
Section: What Mechanisms Link Reduced Somatotropic Signaling With Slomentioning
confidence: 99%
“…This likely represents a shift in the distribution of food-derived energy toward other energetically costly processes and in particular, thermogenesis [94]. However, these animals exhibit normal antibody production in response to a strong challenge [95] and exhibit a delay in immunosenesence [21, 88]. …”
Section: What Mechanisms Link Reduced Somatotropic Signaling With Slomentioning
confidence: 99%
“…The supernatant was discarded and cells were resuspended in 500 L of PBS. Cells stained with monoclonal antibodies were analyzed by flow cytometry with a FACScan Cell Sorter (Becton Dickinson, Mountain View, CA) as previously described [11,29]. For each experiment 5,000 cells with the forward and 90°light scattering characteristics of mononuclear cells were analyzed.…”
Section: Measurement Of Splenic Lymphocyte Subsets and In Vitro Blastmentioning
confidence: 99%
“…NK cells were isolated from peripheral blood as previously published [29]. NK cells (Effector cells; E) at a concentration of 5 ϫ 10 6 cells/mL were mixed with target cells (K562) with concentration of 1 ϫ 10 5 cells/mL at the final E:T ratio of 25:1.…”
Section: Cytotoxic Activity Of Natural Killer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contradiction may be explained by the exercise period (10 months) resulting in aging of B-lymphocytes contributing to the age-related decline in the immune response (Souvannavong et al 1998). A previous study showed that TTspecific antibody titers increased without B cell (CD19 + ) density changes in the peripheral blood (Hall et al 2002). However, increased TT-specific antibody-producing cells (Fig.…”
Section: Discussionmentioning
confidence: 94%